Answer:
a) the intensity of the polarization of light emerging from each filter is <em>I₀/2, </em>0.25 <em>I₀ </em>and 0.125 <em>I₀ </em>
b) the intensity of light emerging from the each remaining filter is <em>I₀ / 2 </em>and <em>0.</em>
Explanation:
a) The intensity of the incident light is <em>I₀ </em>and therefore the intensity of light transmitted through the first filter is
<em>I₁ = I₀ / 2</em>
The polarizing direction will be parallel to the axis of the first filter intensity of light transmitted through the second filter:
<em>I₂</em> = <em>I₁</em> cos²(θ₁)
<em />
<em>I₂</em> = (<em>I₀ </em>/ 2) cos²(45°)
<em>I₂</em> = 0.25 <em>I₀</em>
<em />
<em />
Therefore, the polarizing direction will be at 45° to the axis of the first filter. The light intensity transmitted through the filter will be
<em>I₃</em> = <em>I₂</em> cos²(θ₂ - θ₁)
<em>I₃ </em>= <em>I₂</em> cos²(90 - 45)
<em />
<em>I₃ </em>= <em>I₂</em> cos²(45)
<em>I₃ </em>= 0.25 <em>I₀ </em>cos²(45)
<em>I₃ </em>= 0.125 <em>I₀ </em>
<em />
Therefore, the intensity of the polarization of light emerging from each filter is <em>I₀/2, </em>0.25 <em>I₀ </em>and 0.125 <em>I₀ </em>
<em />
b) the intensity of light transmitted through the first filter is
<em>I</em>₁ = <em>I₀ </em>/ 2
when the second filter is removed.
The intensity of light that is transmitted through the third filter is :
<em>I₃' </em>= <em>I</em>₁ cos²(90)
<em>I₃' </em>= (<em>I₀ </em>/ 2)(0)
<em>I₃' </em>= 0
Therefore, the intensity of light emerging from the each remaining filter is <em>I₀ / 2 </em>and <em>0.</em>